The Strategy of Islamic Boarding School-Owned Enterprises in Supporting Economic and Educational Sustainability at the Nurul Jadid Paiton Probolinggo Islamic Boarding School - Widad Ulfatul Mawaddah Hadi; Umrotul Khasanah; Khusnudin Khusnudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to identify the role of BUMP (Pesantren-Owned Enterprises) in supporting the economic independence of Islamic boarding schools, analyze the forms of BUMP’s contribution to the sustainability of education at Pondok Pesantren Nurul Jadid, and examine the management strategies of BUMP in ensuring the sustainability of both the economic and educational aspects of the pesantren. This study employs a naturalistic qualitative approach with phenomenological analysis, supported by the theoretical frameworks of Sustainable Development Theory, Human Capital Theory, and the Triple Bottom Line. These three theories are applied to examine the relationship among the economic, educational, and social dimensions that are integrated within BUMP’s management system. Thus, this research not only evaluates business success from an economic standpoint but also its contribution to the continuity of education. The findings of the study highlight six main strategies in BUMP management: strengthening Sharia-based governance through SOPs and financial report digitalization; business diversification encompassing trade, laundry, agribusiness, and digital platforms; integrating business with education through skill laboratories and student internships; strengthening alumni networks and strategic partnerships; digitizing financial management with Accurate and IPOS Ultimate applications; and developing a grand design for sustainability that synergizes economic, educational, leadership development, and physical infrastructure aspects. These findings affirm that BUMP can serve as a model for pesantren economic independence that is relevant to the challenges of the modern era while maintaining the identity of Islamic values.